2018
DOI: 10.32598/bcn.9.5.317
|View full text |Cite
|
Sign up to set email alerts
|

Research Paper: Neuroprotective Effect of Quercetin Nanocrystal in a 6-Hydroxydopamine Model of Parkinson Disease: Biochemical and Behavioral Evidence

Abstract: Introduction:Studies have suggested that free radicals-induced neurodegeneration is one of the many studies of Parkinson Disease (PD). Quercetin as a natural polyphenol has been regarded as a significant player in altering the progression of neurodegenerative diseases by protecting from damages caused by free radicals. Owing to its poor water solubility, preparation of its oral formulation is urgently needed. Recently, nanocrystal technique as an effective way has been introduced for oral administration of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…In PD-like rats, the bioavailability and the efficacy of QC nanocrystals were greater than QC alone. A significant enhancement of the antioxidant enzyme activities and total glutathione level, as well as decline in malondialdehyde level were evident in hippocampal area (Ghaffari et al, 2018). Nanoencapsulated QC improved the ischemia reperfusion induced neuronal damage in vivo, probably in association with enhanced neuronal count and elevated antioxidant activity (Ghosh et al, 2013).…”
Section: Quercetin (Qc)mentioning
confidence: 92%
See 1 more Smart Citation
“…In PD-like rats, the bioavailability and the efficacy of QC nanocrystals were greater than QC alone. A significant enhancement of the antioxidant enzyme activities and total glutathione level, as well as decline in malondialdehyde level were evident in hippocampal area (Ghaffari et al, 2018). Nanoencapsulated QC improved the ischemia reperfusion induced neuronal damage in vivo, probably in association with enhanced neuronal count and elevated antioxidant activity (Ghosh et al, 2013).…”
Section: Quercetin (Qc)mentioning
confidence: 92%
“…Despite its beneficial effects, poor solubility and low bioavailability hindered its clinical applications. Accordingly, to control such limitations, alternative QC formulations such as nanocapsules, nanogels, liposomes, nanosuspensions, and microsphere have been recommended, in which QC-nanocapsulation was shown to be the most proper form (Chakraborty et al, 2012;Nathiya et al, 2014;Ghaffari et al, 2018). In a study, QC-loaded nano lipidic carriers (NLCs) improved the QC bioavailability and delivery to the brain, while enhanced its antioxidant activity (Kumar et al, 2016).…”
Section: Quercetin (Qc)mentioning
confidence: 99%
“…The reduction of size in quercetin to the nanometric range will increase its bioavailability at the targeted site, as stated by Ghaffari et al [153]. The 6-hydroxydopamine (6-OHDA) induced Parkinson-like model in male rats was studied by them, who reported that treatment with nanoquercetin prevented the disruption of memory while increasing antioxidant enzymatic activities such as SOD and catalase decreased the Malondialdehyde (MDA) level in the hippocampal area of the brain, thus supporting their provided hypothesis of using quercetin as an anti-Parkinson agent in rats [153]. Similarly, the combination of quercetin with bio-enhancer piperine has been reported [154] to counter 6-OHDA-induced Parkinson's diseases in rats.…”
Section: Quercetin As a Neuroprotective Agentmentioning
confidence: 95%
“…A magnetic stirrer was used to keep the suspension homogenized. Dried curcumin nanocrystals were collected in small bottles and maintained in separate desiccators for further study [32,33].…”
Section: Preparation Of Curcumin Nanocrystalsmentioning
confidence: 99%